Role of chemerin and omentin in predicting ovulatory dysfunction in obese women with polycystic ovary syndrome (PCOS) - Noor Najm Abdullah; Manar Abbas Alameri; Thikra Majid Muhammed; Osama A. Mohsein (Universitas Nahdlatul Ulama Surabaya, 2026)
Polycystic ovary syndrome (PCOS) is an endocrine condition that is characterized by ovulatory dysfunction, hyperandrogenism, and metabolic imbalances. The aim of the study was to assess the predictive ability of chemerin and omentin-1 in ovulatory dysfunction of obese PCOS women. The study is a case-control study conducted at Al-Nasiriyah General Hospital (Jan 2024 – Jun 2025) with a sample size of 150 obese and 70 normal weight women with PCOS and 50 healthy controls. The diagnosis of PCOS was made according to Rotterdam criteria (2003). They included participants aged 18 years to 35 years old, who were not on hormonal therapy in the recent past; pregnancy, endocrine and chronic diseases were excluded. Blood samples were fasted and serum was separated and stored in the refrigerator at 20°C. Hormonal (Follicle-Stimulating Hormone, Luteinizing Hormone, LH/FSH, testosterone, Sex hormone binding globulin), metabolic (glucose, insulin, HOMA-IR, triglycerides, HDL-C), and adipokine (chemerin, omentin-1) levels were measured using ELISA, spectrophotometry, and Cobas e411 kits (Roche, Germany). There were no major differences in terms of age (p=0.63). BMI, waist circumference, menstrual irregularity and family history of PCOS were more prevalent among the obese PCOS women. There was an increase in the LH, LH/FSH ratio and the total testosterone and a decrease in SHBG. The most pronounced metabolic abnormalities were observed in PCOS obese, with lowest HDL-C, and progressively higher levels of metabolic abnormalities with increasing deficiency of ovulatory dysfunction and insulin resistance. There are significant differences in hormonal, metabolic, and ovarian changes in obese and non-obese PCOS women. High levels of chemerin and low levels of omentin-1 are closely related to insulin resistance and ovulatory dysfunction and suggest their use as predictive biomarkers and mediators of metabolic and reproductive pathophysiology in PCOS.